2018
DOI: 10.1016/s2095-3119(18)62064-7
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental blue light increases growth and quality of greenhouse pak choi depending on cultivar and supplemental light intensity

Abstract: To evaluate the supplementary blue light intensity on growth and health-promoting compounds in pak choi (Brassica campestris ssp. chinensis var. communis), four blue light intensity treatments (T0, T50, T100 and T150 indicate 0, 50, 100, and 150 μmol m-2 s-1 , respectively) were applied 10 days before harvest under greenhouse conditions. Both of cultivars (greenand red-leaf pak choi) under T50 had the highest yield, content of chlorophyll and sugars. With light intensity increasing, antioxidant compounds (vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 45 publications
3
40
2
Order By: Relevance
“…A recent study reported a reduction in DPPH antioxidant activity in PC under different pulsed-LED frequencies of yellow (590 nm) LEDs (Vastakaite et al, 2017). Another study found that increasing blue light intensity significantly enhanced DPPH antioxidant activity in two pac choi cultivars (Zheng et al, 2018). Only under a ratio of 18.45A:33.51B:47.48R did we find a significant increase in DPPH antioxidant activity from control in PC microgreens (Table 3).…”
Section: Dpphmentioning
confidence: 61%
“…A recent study reported a reduction in DPPH antioxidant activity in PC under different pulsed-LED frequencies of yellow (590 nm) LEDs (Vastakaite et al, 2017). Another study found that increasing blue light intensity significantly enhanced DPPH antioxidant activity in two pac choi cultivars (Zheng et al, 2018). Only under a ratio of 18.45A:33.51B:47.48R did we find a significant increase in DPPH antioxidant activity from control in PC microgreens (Table 3).…”
Section: Dpphmentioning
confidence: 61%
“…The light environment could affect GLs in brassica species. Higher percentages of blue wavelengths led to a pronounced enhancement of glucosinolate contents in pakchoi [ 53 ]. The accumulation of glucosinolates in Chinese kale sprouts shoots significantly inhibited by 30 μmol m −2 s −1 B LED (470 nm) compared with the darkness control, white LED light and R LED light treatments, while there was no obvious effect on those of the roots [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…butterhead) leaves significantly decreased when the light intensity of red and blue LED light (red:blue = 4:1) increased from 60 to 210 μmol m −2 s −1 [ 37 ]. Before harvest, supplemental blue LED light increased the growth and nutrients of pak choi ( Brassica rapa ) grown in the greenhouse, while the nitrate concentration decreased as the blue light intensity increased from 0 to 150 μmol m −2 s −1 [ 38 ]. Samuolienė et al [ 39 ] used mixed LEDs (those emitting at 455, 638, 665 and 731 nm) with different light intensities to treat Brassica microgreens.…”
Section: Nitrate Assimilation and Accumulation In Vegetables In Rementioning
confidence: 99%